A PRISMA-IPD systematic review and meta-analysis: does age and follow-up improve active range of motion of the wrist and forearm following pediatric upper extremity cerebral palsy surgery? - Song, Amy X.; Saad, Anthony; Hutnik, Lauren; Chandra, Onrina; McGrath, Aleksandra; Chu, Alice (Frontiers in Surgery, 2024)
Purpose: Surgical treatments such as tendon transfers and muscle lengthening play a significant role in cerebral palsy management, but timing of upper extremity cerebral palsy surgery remains controversial. This study systematically reviews the current literature and investigates the correlation between age at surgery and follow-up time with surgical outcomes in pediatric upper extremity cerebral palsy patients. Methods: A comprehensive search of PubMed, Cochrane, Web of Science, and CINAHL databases was performed from inception to July 2020 and articles were screened using PRISMA guidelines to include full-text, English papers. Data analysis was performed using itemized data points for age at surgery, follow-up length, and surgery outcomes, reported as changes in active forearm and wrist motion. A 3D linear model was performed, to analyze the relationship between age, follow-up length, and surgery outcomes. Results: A total of 3855 papers were identified using the search terms and a total of 8 studies with itemized patient data (n=126) were included in the study. The studies overall possessed moderate bias according to the ROBINS-I scale. Regression analysis showed that age is a significant predictor of change (|t| > 2) in active forearm supination (Estimate = -2.3465, Std. Error = 1.0938, t-value= -2.145) and wrist flexion (Estimate = -2.8474, Std. Error = 1.0771, t-value = -2.643) post-intervention, with older individuals showing lesser improvements. The duration of follow-up is a significant predictor of improvement in forearm supination (Estimate = 0.3664, Std. Error = 0.1797, t-value = 2.039) and wrist extension (Estimate = 0.7747, Std. Error = 0.2750, t-value = 2.817). In contrast, forearm pronation (Estimate = -0.23756, Std. Error = 0.09648, t-value = -2.462) and wrist flexion (Estimate = -0.4243, Std. Error = 0.1859, t-value = -2.282) have a significant negative association with follow-up time. Conclusion: These results suggest that there is significant correlation between the age and follow up after surgery with range of motion gains. Most notably, increased age at surgery had a significant negative correlation with select active range of motion postoperative outcomes. Future research should focus on identifying other factors that could affect results of surgical treatment in upper extremity.